SHui, an EU-Chinese cooperative project to optimize soil and water management in agricultural areas in the XXI century - José A. Gómez; Alon Ben-Gal; Juan J. Alarcón; Gabrielle De Lannoy; Shannon de Roos; Tomáš Dostál; Elias Fereres; Diego S. Intrigliolo; Josef Krása; Andreas Klik; Gunther Liebhard; Reinhard Nolz; et al. (International Soil and Water Conservation Research, 2020)
This article outlines the major scientific objectives of the SHui project that seeks to optimize soil and water use in agricultural systems in the EU and China, by considering major current scientific challenges in this area. SHui (for Soil Hydrology research platform underpinning innovation to manage water scarcity in European and Chinese cropping systems) is large cooperative project that aims to provide significant advances through transdisciplinary research at multiple scales (plot, field, catchment and region). This paper explains our research platform of long-term experiments established at plot scale, approaches taken to integrate crop and hydrological models at field scale; coupled crop models and satellite-based observations at regional scales; decision support systems for specific farming situations; and the integration of these technologies to provide policy recommendations through socio-economic analysis of the impact of soil and water saving technologies. It also outlines the training of stakeholders to develop a basic common curriculum despite the subject being distributed across different disciplines and professions. As such, this article provides a review of major challenges for improving soil and water use in EU and China as well as information about the potential to access information made available by SHui, and to allow others to engage with the project. Keywords: Yield, Sustainability, Cropping, Cooperation